2023
DOI: 10.1021/acsaem.3c00053
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectrochemically Induced CO2 Reduction Using Halide-Tunable Lead-Free Perovskites

Abstract: We report on a series of ambient processed, all-inorganic, leadfree nanocrystalline perovskites, viz. Cs 3 Bi 2 Cl 9−x Br x , which are halide-tunable and demonstrate photocatalytic CO 2 reduction. The conversion yield of CO 2 to CO could be tuned by meticulously regulating the Cl-to-Br ratio within the perovskite material. While all of the samples demonstrated CO 2 reduction purely under photoillumination (i.e., illumination with an applied bias of 0 V vs Ag/AgCl), it was remarkable that the conversion yield … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 58 publications
1
1
0
Order By: Relevance
“…Figure b compares the instantaneous photocurrent responses of different samples. Under light, the photocurrent intensity of the TCE sample is significantly higher than that of T vs CE, which also further confirms that the heterogeneous structure of TCE is more conducive to charge transfer and can help the photocatalytic reaction to proceed …”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…Figure b compares the instantaneous photocurrent responses of different samples. Under light, the photocurrent intensity of the TCE sample is significantly higher than that of T vs CE, which also further confirms that the heterogeneous structure of TCE is more conducive to charge transfer and can help the photocatalytic reaction to proceed …”
Section: Resultssupporting
confidence: 57%
“…Under light, the photocurrent intensity of the TCE sample is significantly higher than that of T vs CE, which also further confirms that the heterogeneous structure of TCE is more conducive to charge transfer and can help the photocatalytic reaction to proceed. 56 To investigate the photocatalytic mechanism, the Mott− Schottky curves of samples T and CE were tested, and it can be found that the slopes of the MS curves of T versus CE are positive at different frequencies (500, 1000, and 1500 Hz), which indicates that our prepared TiO 2 with CdS is a typical ntype semiconductor. The flat-band potentials of T and CE were obtained from the tangent intercepts of the MS curves on the x-axis as −0.53 and −0.73 V (vs Ag/AgCl, pH = 7) (Figure 4c,d), and the conduction-band (CB) potentials of the n-type semiconductors in general are lower than the flat-band (FB) potentials by 0.1−0.3 eV; 57 it is then based on eqs 1 and 2: 58…”
Section: Characterization Of Materialsmentioning
confidence: 92%
“…In addition to being extensively studied in solar cells and photodetectors, trivalent and tetravalent metal cation lead-free perovskites have also exhibited preliminary developments in capacitors, photocatalysts, and other fields. [252][253][254][255][256][257] Pious et al fabricated an MA 3 Bi 2 I 9 perovskite electrochemical double-layer capacitor (EDLC) with the maximum areal capacitance of 5.5 mF cm À2 at a scan rate of 5 mV s À1 , which is the highest performance among hybrid perovskite-based EDLCs. 258 The stability studies indicated that after 10 000 charge-discharge cycles, the capacitance still retained 84.8% of the original value, and thus this device showed good device operation stability.…”
Section: Other Applicationsmentioning
confidence: 99%
“…[12,13] Most of the perovskites, based on APbX 3 (A = Cs + , MA + ; methylammonium, X = Br À , I À and various halide combinations) have proven to be efficient photocatalysts in the oxidation of aromatic compounds such as 2mercaptobenzothiazole, [14,15] β-naphthol, [16] catalyst-based organic chemical reactions, [17,18] as well as in photo-(electro)chemical (PEC) H 2 generation and CO 2 transformation to CO, CH 4 with a high selectivity towards these products. [19][20][21] Unfortunately, the presence of toxic metals such as Pb runs counter to environmental protection and hinders the eventual scaling up and subsequent commercialization of Pb-perovskites. Consequently, this scenario contemplates an interesting opportunity for research groups to explore new synthetic routes, producing lead-free halide perovskites (LFHPs), that exhibit similar or superior intrinsic properties and long-term stability.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, halide perovskites are considered suitable candidates, considering their outstanding light‐harvesting capabilities in a broad range of wavelengths from the energy spectrum, a modulable band gap in the visible/IR region, and thereby a controllable band structure, versatile surface chemistry and improved electronic features [12,13] . Most of the perovskites, based on APbX 3 (A=Cs + , MA + ; methylammonium, X=Br − , I − and various halide combinations) have proven to be efficient photocatalysts in the oxidation of aromatic compounds such as 2‐mercaptobenzothiazole, [14,15] β‐naphthol, [16] catalyst‐based organic chemical reactions, [17,18] as well as in photo(electro)chemical (PEC) H 2 generation and CO 2 transformation to CO, CH 4 with a high selectivity towards these products [19–21] …”
Section: Introductionmentioning
confidence: 99%